Association Between Renin Angiotensin Aldosterone System and Severity of Pre-eclampsia - HALA A. AL-MOAYED (International Journal of Pharma and Bio Sciences, 2018)
Study the changes in different biochemical parameters of the renin angiotensin aldosterone system that occur in pre-eclampsia (mild and severe). The study involved 90 pregnant women, of gestational age from 36 to 40 weeks. The age of the pregnant women ranged between 20 and 40 years. The subjects in this study were divided into three groups: First group: 30 normotensive pregnant women. Second group: 30 pregnant women with mild pre-eclampsia. Third group: 30 pregnant women with severe pre-eclampsia. Placental tissue was obtained after delivery and assays were performed by ELISA (Soluble pro renin receptor assay kit). Blood sampling was performed after 1-2 min. Plasma samples were used to measure plasma soluble pro renin receptor using ELISA (Soluble pro renin receptor assay kit), plasma aldosterone, and plasma renin activity using ELISA assay (Labor diagnostika Nord LDN). Serum samples were used to measure serum sodium and potassium. Blood pressure was measured for all pregnant women. Results: - There was a significant increase in mean of placental (P)RR and maternal s(P)RR in mild and severe pre-eclampsia group when compared with control pregnant group, and there was also a significant increase in mean of placental (P)RR and maternal s(P)RR in severe preeclampsia group when compared mild pre-eclampsia. There was a significant decrease in the mean of aldosterone and plasma renin activity in mild and severe pre-eclampsia when compared with control pregnant group, and there was a significant decrease in mean of aldosterone in severe pre-eclampsia group when compared mild pre-eclampsia, while there was insignificant difference in plasma renin activity in severe pre-eclampsia group when compared to mild pre-eclampsia. In conclusion the placental pro renin receptor, plasma Soluble pro renin receptor were significantly increased in preeclampsia in proportion with the severity, and the placental pro renin receptor was having the highest diagnostic accuracy.